Tracing female resilience in KL Noir: magic through the lenses of psychogeography and carnivalesque - Seach, Jin Beng (Penerbit Universiti Kebangsaan Malaysia, 2024)
The locations around us have a profound influence on our actions, thoughts, and behaviours. The major capitals around the world have served as settings for many fictional works that showcase how the psyches of the characters have changed when interacting with these locations. Kuala Lumpur, being one of the bustling cities in Southeast Asia, is no exception. The beauty and vibrancy of the metropolis have been highlighted in numerous creative works. However, its depiction is significantly different in the KL Noir series, which emphasises the darkness and bleakness of a location. In the collection of short stories, KL Noir: Magic (2021), the city plays a pivotal role in influencing and shaping the life trajectories of the characters. This study aims to examine how female characters in selected stories from the anthology are able to build their resilience within the city through the lens of psychogeography. Examined alongside Mikhal Bakhtin's concept of the Carnivalesque, the characters' abilities to inverse social hierarchy and create a temporal escape as they engage with their surroundings within Kuala Lumpur are explored. The diverse set of female characters found within the selected stories consists of struggling working-class women, a retiree, a robot, and ghosts; it establishes a more robust connection between these characters and the city. Finally, the study shows how the effects of psychogeography and carnivalesque are able to transcend various forms of female existence and lead to female resilience.